A reconciling hypothesis centred on brain-derived neurotrophic factor to explain neuropsychiatric manifestations in rheumatoid arthritis. (22nd January 2021) - Pedard, Martin; Quirié, Aurore; Tessier, Anne; Garnier, Philippe; Totoson, Perle; Demougeot, Céline; Marie, Christine
Abstract: Rheumatoid arthritis (RA) is an autoimmune chronic inflammatory disease characterized by synovitis leading to joint destruction, pain and disability. Despite efficient antirheumatic drugs, neuropsychiatric troubles including depression and cognitive dysfunction are common in RA but the underlying mechanisms are unclear. However, converging evidence strongly suggests that deficit in brain-derived neurotrophic factor (BDNF) signalling contributes to impaired cognition and depression. Therefore, this review summarizes the current knowledge on BDNF in RA, proposes possible mechanisms linking RA and brain BDNF deficiency including neuroinflammation, cerebral endothelial dysfunction and sedentary behaviour, and discusses neuromuscular electrical stimulation as an attractive therapeutic option.